Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.ppat.1002627
|View full text |Cite|
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Dengue-Virus Entry

Abstract: Flavivirus envelope protein (E) mediates membrane fusion and viral entry from endosomes. A low-pH induced, dimer-to-trimer rearrangement and reconfiguration of the membrane-proximal “stem" of the E ectodomain draw together the viral and cellular membranes. We found stem-derived peptides from dengue virus (DV) bind stem-less E trimer and mimic the stem-reconfiguration step in the fusion pathway. We adapted this experiment as a high-throughput screen for small molecules that block peptide binding and thus may in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 33 publications
3
84
0
Order By: Relevance
“…Vero cells were grown in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS). The HEK293T, BHK21, Huh7.5, C6/36 cells were grown as previously described (7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vero cells were grown in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS). The HEK293T, BHK21, Huh7.5, C6/36 cells were grown as previously described (7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…The virus sources are noted in parentheses: DENV-2 strain NGC (L. Gehrke), Kunjin virus (M. Diamond), Modoc virus (ATCC VR-1260), vesicular stomatitis virus (VSV) (S. Whelan), and poliovirus 1 (PV1) (ATCC VR-1562). Infections of Vero cells with these viruses were performed as previously described for DENV-2 (7,9), and viral titers were determined by a plaque formation assay. Hepatitis C virus (HCV) Japanese fulminant hepatitis strain 1 (JFH1) was produced from linearized pJFH-1 plasmid (T. Wakita).…”
Section: Methodsmentioning
confidence: 99%
“…As there is no effective clinical therapeutic intervention in flaviviral infection, the identification of novel inhibitors to target the virus life cycle is urgently required (Geiss et al, 2009;Shi, 2002). The E protein of flaviviruses mediates interactions between the virus and host cells during the initial stages of infection; hence it is widely targeted for the development of antiviral molecules, including inhibitory peptides (Bai et al, 2007;Costin et al, 2010;Hrobowski et al, 2005), therapeutic antibodies (Thompson et al, 2009) and small molecules (Kampmann et al, 2009;Schmidt et al, 2012). Here, we have established a new approach for antiviral screening targeted to JEV E, and in particular to its role in the attachment and fusion processes.…”
Section: Discussionmentioning
confidence: 99%
“…7C) suggests that HCV II-1 either locks the viral envelope in its prefusion state or promotes an envelope conformation change that is incapable of fusion. Along these lines, it has been observed that the Dengue2 entry inhibitor 1662G07 blocks viral fusion by stabilizing an intermediate conformation of the Dengue2 viral envelope that cannot complete the fusion-promoting conformational change (37). Further studies will be necessary to elucidate how HCV II-1 prevents HCV particles from fusing with the endosome whether through a direct interaction with E2 or other means.…”
Section: Discussionmentioning
confidence: 99%